I need some help proving the following:

Let $A \in M_{n \times n}$ be a diagonalizable matrix with distinct eigenvalues $\lambda_1, \ldots , \lambda_k$ and corresponding multiplicities $d_1, \ldots, d_k$. Given that $S = \{B \in M_n \,|\, AB = BA\}$, prove that $\dim (S) = d_1^2 + \cdots + d_k^2$.

Here's what I've done:

Since $A$ is diagonalizable, we have that $D = P^{-1}AP$, where $D$ is a diagonal matrix. We may then write, $$P^{-1}AP = \begin{bmatrix}\Lambda_1 & & & \\ & \Lambda_2 & & \\ & & \ddots & \\ & & & \Lambda_k\end{bmatrix} = D,$$ where $$\Lambda_i = \underbrace{\begin{bmatrix}\lambda_i & & & \\ & \lambda_i & & \\ & & \ddots & \\ & & & \lambda_i\end{bmatrix}}_{d_i \, \text {columns}}.$$

Obviously the size of each $\Lambda_i$ is $d_i \times d_i = d_i^2$, which I'm thinking we need to show that each block contributes this to the total dimension as we work along the diagonal, but I'm having a little trouble coming to this conclusion via the why and how.

Clearly each column vector of $D$ and consequently each column vector of each $\Lambda_i$ is linearly independent, but I am unable to see what comes next to receive the squared part. Can someone provide a hint as to how I can make this conclusion?


Hint: Write $D$ as a block matrix $$ D= \pmatrix{ \lambda_1 I \\ & \lambda_2 I \\ && \ddots \\ &&& \lambda_k I } $$ Noting that $$ P^{-1}[AB]P= D(P^{-1} BP), \qquad P^{-1}[BA]P= (P^{-1} BP)D $$ It suffices to determine which matrices $M$ satisfy $MD=DM$.

To that end, write $M$ as a block matrix (partitioned in the same way as $D$), and compute the products $DM$ and $MD$. Determine that all blocks of $M$ must be zero except those on the diagonal.

  • $\begingroup$ @MartinSleziak Thank you for the bounty! $\endgroup$ – Ben Grossmann Jun 23 '19 at 13:25

Hint. Let $B = [b_{ij}]$ be a $n\times n$ matrix which commutes with a diagonal matrix $D=\mbox{diag}(\lambda_1,\lambda_2,\dots,\lambda_n)$, that is $DB=BD$.

Then by computing $DB$ and $BD$, we get that for all $1\leq i,j\leq n$, $$\lambda_i b_{ij} = b_{ij}\lambda_j$$ which implies that $(\lambda_i - \lambda_j) b_{ij} = 0$. Hence either $\lambda_i = \lambda_j$ or $b_{ij} = 0$.


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.